Reward, Perceived Organizational and Supervisor Support (POS), Work Life Balance sebagai Faktor Kinerja Karyawan melalui Employee Engagement - Tri Wahyu Nurcahyo (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2021)
The purpose of this research is to analyze the effect of reward, Perceived Organization and Supervisor Support (POS) and work-life balance on employee performance through employee engagement. The number of respondents in this study amounted to 75 respondents with purposive sampling technique. This study uses a quantitative approach using SPSS data analysis. Based on the results of the analysis, it can be concluded that there is a simultaneous influence between reward, Perceived Organization and Supervisor Support (POS) and work-life balance on employee performance through employee engagement. Keywords: employee performance, reward, perceived organization and supervisor support (POS), work-life balance, employee engagement